Fish community turnover in a dammed Andean River over time (2022)
ABSTRACT: We describe the change in the fish community of the Porce River in Magdalena River Basin, Colombia, following the construction of the Porce III hydropower reservoir based on 13 years of monitoring data. The results show a clear reduction of the number of native species, which have been supplanted by colonizing non-native species, especially in the reservoir. Four native species detected prior to dam construction have apparently disappeared, but 12 new species were registered post-construction. We analyzed spatial changes in beta diversity in the aquatic environments surrounding the dam. The new environment generated by the reservoir presents a unique species composition and contributes significantly to the total beta diversity of the system. Altogether three distinct new fish assemblages emerged following reservoir formation and there are now six assemblages where there had previously been three. This dramatic change, already visible within a decade of construction, highlights just how strong of an impact dam construction has on habitats and how rapidly fish communities react in this hotspot for endemic fish diversity. Our findings demonstrate the importance of monitoring fish communities for revealing the impact of damming on river ecosystems and informs potential complementary fish diversity inventories elsewhere in the Magdalena River basin.